O uso das TICs como estratégia para promover o conhecimento em Tabela Periódica - Rodrigues, Irivan Alves (2019)
The technological evolution has brought great positive impacts to the school environment. This process guides teaching and learning through information and communication technologies (ICTs) that enable teachers to use the various educational tools and approaches. The search for methodological alternatives to improve the effectiveness of the teaching and learning process in relation to the Periodic Table content, making them more enjoyable for teachers and students in the classroom, was the focus of this study. The use of digital games, with an educational character, was the strategy applied to enhance the quality of the result, because through the resources offered by the games, learning acquires a playful bias, which enables a more dynamic and pleasant teaching and learning process. In this context, this work sought to discuss the importance of ICTs and to contribute to the improvement of teaching learning of the Periodic Table content, using methodological strategies through digital educational games that encourage the learning of the students involved. These were applied in a state public school, in the city of Santa Rita-PB, for two first-year high school classes. The methodology was developed with a sequence of activities, through lectures, use of electronic educational media in cell phones/computers and questionnaires containing open and closed questions, applied to the theme. The use of digital resources in this work, as a pedagogical proposal, aimed at complementing the traditional teaching methodology, to construct the knowledge of the participants in an interactive way, as well as to promote the development of skills and reasoning. The ICTs used provided motivating and dynamic classes for the students, which obtained significant gains in learning and time efficiency for solving problems involving the topic of Periodic Table. The data showed that, after making use of digital games, the average percentage in the number of correct answers to the questions addressing the Periodic Table content went from 71.0% to 90.4%. As a result of this work, a didactic-pedagogical primer was developed as an educational product, aimed at teachers of High School Chemistry and related areas.